Pelaksanaan Pembelajaran Orientasi Mobilitas - Sosial Komunikasi (OM-SK) pada Peserta Didik Tunanetra di SLB Negeri 2 Padang - Puspitasari, Adelia; Taufan, Johandri (Universitas Negeri Padang, 2023)
This research aims to provide an overview of the implementation of Orientation and Mobility and Social Skills (OM-SK) learning at SLB N 2 Padang aimed at teachers and blind students. The method used in this research is descriptive qualitative, with research subjects consisting of teachers, blind students, school principals, and parents. Data was collected through observation, interviews, and documentation studies, and data analysis was carried out through three stages: data reduction, data presentation, and conclusions. To ensure the validity of the data, degrees of trust, transferability, attachment and certainty are used. The research results show that OM-SK learning always begins with a diagnostic assessment as a guide for learning design. OM-SK learning consists of introductory, core and closing activities face to face once a week for one hour of learning. Learning evaluation is carried out through summative and formative assessments. The implementation of OM-SK learning has obstacles and efforts to overcome these obstacles.